3D micro‐CT analysis of the interface voids associated with Thermafil root fillings used with AH Plus or a flowable MTA sealer. (8th October 2012) - Gandolfi, M. G.; Parrilli, A. P.; Fini, M.; Prati, C.; Dummer, P. M. H.
Abstract Aim To investigate nondestructively the percentage of 3D voids and marginal gaps in a pre‐defined interface volume of interest (VOI) within root fillings produced by Thermafil Obturators with either a hydrophobic epoxy‐resin‐based sealer (AH Plus) or a hydrophilic flowable calcium‐silicate sealer [mineral trioxide aggregate (MTA) Flow]. Methodology Sixteen single root canals from extracted premolar teeth were prepared with ProTaper rotary instruments, randomly allocated into two groups (n = 8) and filled with size 30 Thermafil Obturators in association with AH Plus or MTA Flow sealers. The filled roots were stored at 37 °C in 5 mL of Hank's balanced salt solution (HBSS) used to represent body fluids and scanned after 7 days and 6 months using a high‐resolution micro‐CT. From each root, images of 3000 sections were analysed in 3D and binarized using a high‐resolution micro‐CT (4‐μ resolution). The 3D distribution of voids (porosity and marginal gaps) at the gutta‐percha‐sealer‐dentine interface was detected through a threshold grey level and expressed as percentage of the 40‐μ‐thick pre‐defined interface VOI (20 μ of interface dentine and 20 μ of gutta‐percha/sealer). A method of analysis based on the root canal segmentation was used, and coronal, middle and apical thirds considered separately. The percentage of 3D void volume was compared statistically using one‐way anova (significance for P < 0.05). Environmental Scanning Electron Microscope with Energy Dispersive X‐ray (ESEM‐EDX) analysis was performed on the surface of both sealers after soaking in HBSS. Results Micro‐CT detected gaps at the dentine‐sealer interface in both groups. Void volumes wider than 10.21 μm3 with 1.35 μm diameter were detected. Cul‐de‐sac‐type voids (blind pores) and through‐and‐through voids (continuous pores) were discriminated. The apical thirds had a significantly lower 3D void volume (P < 0.05) than the middle and coronal thirds. The 3D void volume reduced significantly (P < 0.05) over time. ESEM‐EDX analysis revealed that MTA Flow sealer created a dense apatite layer after 7 days of immersion in HBSS, whilst only sparse calcium phosphate deposits were detected on AH Plus even after 28 days. Conclusions Micro‐CT proved to be a powerful nondestructive 3D analysis tool for visualizing the porous internal microstructure of dental/endodontic materials at the interface with dentine. The proportion of voids was least in the apical third of root canals. Voids reduced over time in the presence of simulated body fluid.